2022
DOI: 10.1097/mat.0000000000001843
|View full text |Cite
|
Sign up to set email alerts
|

Explainable Machine Learning Analysis of Right Heart Failure After Left Ventricular Assist Device Implantation

Abstract: Right heart failure (RHF) remains a common and serious complication after durable left ventricular assist device (LVAD) implantation. We used explainable machine learning (ML) methods to derive novel insights into preimplant patient factors associated with RHF. Continuous-flow LVAD implantations from 2008 to 2017 in the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) were included. A total of 186 preimplant patient factors were analyzed and the primary outcome was 30 days of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…2 This study considered four strategies: 1) splitting the data into training and test groups, 2) using repeated cross-validation for training the model, 3) employing big data that includes approximately 12,000 patients, 4) applying XGBoost which has been effectively used in the healthcare field for disease diagnosis and risk prediction. 15,16 The reported, well-calibrated XGBoost model achieved a high AUC-ROC (C statistics) of 0.80 compared to AUC of 0.53–0.65 reported in a recent (2020) external validation study of 20 RHF models by Frankfurter et al 2 and a very recently published model of early RHF by Bahl et al 17 (AUC = 0.67). The test dataset in the present model comprised 2,393 patients that were randomly chosen from a large national registry from more than 180 hospitals.…”
Section: Discussionmentioning
confidence: 64%
“…2 This study considered four strategies: 1) splitting the data into training and test groups, 2) using repeated cross-validation for training the model, 3) employing big data that includes approximately 12,000 patients, 4) applying XGBoost which has been effectively used in the healthcare field for disease diagnosis and risk prediction. 15,16 The reported, well-calibrated XGBoost model achieved a high AUC-ROC (C statistics) of 0.80 compared to AUC of 0.53–0.65 reported in a recent (2020) external validation study of 20 RHF models by Frankfurter et al 2 and a very recently published model of early RHF by Bahl et al 17 (AUC = 0.67). The test dataset in the present model comprised 2,393 patients that were randomly chosen from a large national registry from more than 180 hospitals.…”
Section: Discussionmentioning
confidence: 64%
“…For example, Loghmanpour et al found that the systolic PAP, pre-albumin, LDH, and RV EF were most important predictive parameters, and they achieved an impressive AUC rate in their study [57]. Similarly, Kilic et al and Bahl et al identified more predictive parameters and non-linear relationships between preoperative clinical parameters, which is one of the main strengths of AI-based investigations as it is very difficult to infer these relationships through statistical analysis [61,62,64].…”
Section: Discussionmentioning
confidence: 99%
“…The study that was designed by Bahl et al was one of the newest studies that focused on ML and RHF [64]. They preferred an "explainable" ML method called boosted decision trees in order to analyze the preimplant patient factors in nonlinear interactions with RHF after LVAD implantation.…”
Section: Ai-based Studies/risk Scoresmentioning
confidence: 99%
“…The majority of our study population had, therefore, an INTERMACS profile ranging from I to III, a condition at high risk of post-operative morbidity and mortality. 38,39 We found a threshold value of PAPi at 2.84 to predict the risk of early death within 3 months after surgery. This was the median value of PAPi in our study population.…”
mentioning
confidence: 86%